2001
DOI: 10.1179/acb.2001.026
|View full text |Cite
|
Sign up to set email alerts
|

Registration of Interstitial Lung Diseases by 20 Centres of Respiratory Medicine in Flanders

Abstract: We report the results of a prospective registration of the prevalence of interstitial lung diseases by 20 centres of respiratory medicine in Flanders from January 1992 till July 1996. The 20 centres registered a total of 362 cases. Sarcoidosis (31% with inclusion of stage I, or 22% without stage I), idiopathic pulmonary fibrosis (20%), hypersensitivity pneumonitis (13%) and unclassified forms of interstitial lung diseases (9%) were the most often diagnosed diseases. The mean age of the patients was 52 +/- 17 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
101
3
17

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(131 citation statements)
references
References 22 publications
10
101
3
17
Order By: Relevance
“…National registries and multicenter studies have shown that CTD-ILDs constitute 7-21% of all ILDs (22)(23)(24)(25). All patients diagnosed with ILD should be evaluated for potential CTD-ILD by a rheumatologist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…National registries and multicenter studies have shown that CTD-ILDs constitute 7-21% of all ILDs (22)(23)(24)(25). All patients diagnosed with ILD should be evaluated for potential CTD-ILD by a rheumatologist.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that ILDs are more common in males, but CTD-ILDs are more common in females (22)(23)(24)(25)(26). Females are also prone to other autoimmune diseases as well (6,15,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…4 Belçika'da yapılan 20 merkezli bir çalışmada, 360 İAH hastasının %3'ünde PLHH saptanmıştır. 5 Japonya'da prevalansı erkekler ve kadınlar için sırasıyla 0,27/100.000 ve 0,07/100.000 olarak bulunmuştur. 6 PLHH patogenezi bilinmemektedir, ancak sigaranın tetikleyici bir faktör olduğu dü-şünülmektedir.…”
Section: Discussionunclassified
“…8,9,10,11 PLHH, 20-40 yaşlarında pik yapar ve erkeklerde biraz daha sık görülür. 5,8,9 Ancak bu sıklık erkeklerde sigara içme alışkanlığının daha çok olması ile ilişkili olabilir. Bizim de ilk olgumuz 24, ikinci olgumuz 39 yaşında erkeklerdi ve sırasıyla 18 paket/yıl ve 20 paket/yıl sigara öyküsü vermişlerdi.…”
Section: Discussionunclassified
“…In general, early studies tended to involve clinicians collating cases from their local area [3,4] or asking interested colleagues to contribute to registries [5,6], whereas later studies have made use of large databases collected for clinical care or administrative reasons [7][8][9][10]. These later studies boasted far greater numbers, though with some concern about the validity of the cases, the reliability of clinical coding and generalisability to the wider population.…”
mentioning
confidence: 99%